Find a solution to the following system of equations. -3x+3y = -9 -3x + y = 7

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Find a solution to the following system of equations. -3x+3y = -9 -3x + y = 7

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

(–5, –8) (5, 2) (–2, 2) (0, 7)
the first course of action here is to eliminate a variable.....either x or y, it does not matter. I believe it would be easier to eliminate the x's. -3x + 3y = -9 -- multiply everything by -1 -3x + y = 7 ----------- 3x - 3y = 9 (result of multiplying by -1) -3x + y = 7 -----------add -2y = 16 -- divide by -2 y = -8 then sub -8 back in for y in either of the original equations to find x do you have any questions about what I just did ?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

now if you wanted to eliminate the y's instead of the x's, you would have multiplied the second equation by -3.....then added the equations together. But either way, you should arrive at the same answer.
27?
or 24?
@LegendarySadist can u help?
Just sub y=8 back into -3x + y = 7 and solve for x.
Whoops, that would be y=-8
so -11?
hopefully you understand how y = -8 what you do from here is replace every copy of 'y' in an equation like -3x + y = 7 and solve for x -3x + y = 7 -3x + (-8) = 7 ... replace y with -8 -3x - 8 = 7 -3x - 8+8 = 7+8 ... Add 8 to both sides. -3x + 0 = 15 -3x = 15 -3x/(-3) = 15/(-3) ... Divide both sides by -3 to fully isolate x. 1x/1 = -5 1x = -5 x = -5
So together, x = -5 and y = -8 forming the ordered pair (-5,-8) if you were to graph the two lines, the point (-5,-8) would be on both lines. It is the point of intersection between the two lines
Yes I understand and oh okay thank you
ok great

Not the answer you are looking for?

Search for more explanations.

Ask your own question